Sustaining Islamic Values through Institutional Innovation: A Case Study of an Indonesian Vocational Pesantren - Waziroh, Iro; Fuadi, Imam; Kholis, Nur; Adiyono; Kandiri (Al-Hayat: Journal of Islamic Education, 2026)
This study aims to examine how Pondok Pesantren Manbaul Ulum in Indonesia implements management innovation strategies to develop its Vocational Secondary School (VSS) while preserving its core Islamic values in an increasingly competitive vocational education landscape. Employing a qualitative single-case study design, the research collected data through semi-structured interviews with 10 purposively selected informants, representing leaders, curriculum developers, teachers, and students, supplemented by participatory observation and document analysis. Methodological triangulation, member checking, and peer debriefing ensured data validity, and analysis followed Miles, Huberman, and Saldaña’s interactive model. The findings demonstrate that the pesantren’s success is anchored in a deliberate model of institutional hybridity operationalised through a structured dual-curriculum, a disciplinary system that converts piety into a strategic VRIN resource, and a market positioning strategy centred on producing morally grounded graduates. These mechanisms create a synergistic fusion of religious and vocational logics that strengthens organisational resilience and competitive advantage. The study's limitations include its reliance on a single case in one geographical context, which restricts generalizability, suggesting that future research should examine diverse pesantren models or employ mixed methods. This study offers originality by providing a process-based explanation of how faith-based institutions can transform religious values into strategic resources, contributing to institutional theory and offering practical guidance for religious educational organisations navigating modernisation.